Socially Responsible Investment in General Equilibrium - Andrea Beltratti (Fondazione Eni Enrico Mattei (FEEM), 2003)
Socially responsible investment in analyzed in a general equilibrium context. This is important in order to understand the ultimate consequences of SRI on the decisions of economic agents. Building on models by Brock (1982) and Merton (1987), SRI is modelled as the choice to voluntarily give up investment in stocks and bonds issues by a firm producing an externality. The model is used to analyze the utility costs of SRI to the responsible investor and the impact on the price of the stock issued by the firm which is responsible for the externality. The results shed light on the factors which may magnify or reduce the impact of SRI, among which are crucial the wealth commended in relative terms by the responsible agents and the diversification possibilities offered by the firms which are excluded from the investment opportunity set. A set of firms targeted by SRI may be seriously affected by SRI only if the responsible investors command a large portion of overall wealth; moreover the same firms are more likely to be hit by SRI behavior if they do not represent important diversification instruments. Firms with unique characteristics from the point of view of overall diversification are less likely to be the target of SRI.
Keywords: D50; H23; H41; 330; General equilibrium; Redistributive effects; Public goods; Kapitalanlage; Externer Effekt; Umverteilung; Allgemeines Gleichgewicht; Theorie; Sozialverträglichkeit